The Effects of Compliments on the Feelings of Job Attitudes of Hotel Employees - Cheon, Yong-Soo (International Review of Management and Marketing, 2016)
Hardly found is research clarifying the correlation between an individual's attitude change and compliment, through its positive measurement. In particular, it is much harder to find research that verifies such effects with hotel employees, who are highly dependent on personal services through a positive mechanism of compliments. This research, therefore, aims to propose a plan that can be utilized for future management of human resources in the hotel industry by clarifying the effects of compliments on the job attitude of hotel employees from first-class hotels in the Busan region. Results suggest that: The dependent variable – feelings of job attitude – is measured by both personal and organizational aspects. A simple regression model is used to test hypotheses 1 and 2, in which the results verify that both have statistically significant effects. Between the two, personal attitude shows higher influence. This indicates that verbal compliments have larger impacts on job attitude than institutional rewards related to human resource management, such as promotion or compensation. Conclusion suggests that compliments are not burdensome yet more efficient through frequent use. Keywords: Compliment, personal attitude, organizational attitude JEL Classifications: J5, L2, L8, M1, Z31